Ekoland: The Development of Android-Based Learning Media Using iSpring Suite to Improve the Understanding of Ecosystem Material in Elementary School - Badawi, Badawi; Utami, Purie Nawa; Elizar, Elizar; Rohmani, Rohmani; Masitoh, Masitoh; Rachmatia, Meutia (Universitas Pendidikan Indonesia, 2023)
This research aimed to develop science teaching media in the form of learning applications that use the help of iSpring Suite. The development of ecosystem material science learning applications is made to maximize the use of smartphones owned by students and reduce the various negative impacts of using Android in learning. The Research and Development (RD) method using a procedural model, was applied in this research. The data collection instruments in this study were validation sheets, student response questionnaires, and test questions. The test subjects in this study were 48 fifth-grade students at Ibnu Rusyd Islamic Elementary School. The Ekoland learning media feasibility test result is 71.95% from the percentage criteria of 61%-80% which shows very feasible results. and declared feasible because it is greater than 61%. The effectiveness level of Ekoland learning media is 93.75% from the percentage criteria of 61% -80% which shows decent results, and it is said to be effective because it is greater than 80%. Based on the results of the study, it is stated that the development of Ekoland learning media developed with android-based using the iSpring Suite application influences the increase in student learning outcomes in understanding ecosystem material in science learning and can provide a positive response from the use of android that maximizes the benefits of using android in education. Research has had a positive impact on improving science learning in schools, showing that Ecoland has a positive impact on students' learning outcomes and understanding of ecosystems.